Analisis Tingkat Permodalan Bank Hasil Spin-off dan Non Spin-Off - Tyas Ayu Mahanani (Tauhidinomics: Journal of Islamic Banking and Economics, 2022)
The purpose of this research was to analyze the influence of the policy of Spin-off, FDR, ROA, NPF, Total Assets affect the level of capital of Sharia Commercial Banks resulting from Spin-off and Non Spin-off. This research uses panel regression by using the dummy equation to analyze the effect of the spin-off policy on the capital level (CAR). The results showed that the variable dummy Spin-off and total assets had negative impact on CAR. Besides that, this research also shows that FDR and ROA had a positive impact on CAR. Next, NPF does not had impact on CAR. Based on these results, it shows that the Bank's Spin-off and Non-Spin-off results in slow capital growth rates.